Synthesis of orthorhombic chromium boride by solid state reaction - Mao, W.; Bao, K.; Liu, G.; Xie, H.; Chen, C.; Ye, L.; Li, B.; Zhao, X. (Сверхтвердые материалы, 2016)
Chromium boride is characterized by interesting properties, like high melting point, hardness, and corrosion and abrasion resistances. In this paper a novel synthesis of chromium boride micropaticles via a solid-state route at 600 °C is reported. The X-ray diffraction pattern taken from the reaction product indicated that the product was orthorhombic chromium boride. The CrB particle size (about 1~2 μm) is confirmed by FESEM and TEM images. Solid state reactions that were carried out in sealed autoclave systems provide an alternative, convenient, and environmentally friendly pathway for the fabrication of CrB. Повідомляється про новий твердотільний метод синтезу при 600 °C борида хрому CrB, який характеризується такими цікавими властивостями, як високі температура плавлення і твердість, опір корозії і абразивного зносу. Діаграма рентгенівської дифракції продукту реакції свідчила про те, що продукт є орторомбическим боридом хрому. Розмір (~ 1–2 мкм) частинок CrB підтверджується FESEM і ТЕМ-зображеннями. Твердотільні реакції, проведені в герметичних автоклавах, забезпечили альтернативний, зручний, екологічно чистий шлях виробництва CrB. Сообщается о новом твердотельном методе синтеза при 600 °C борида хрома CrB, который характеризуется такими интересными свойствами, как высокие температура плавления и, твердость, сопротивление коррозии и абразивному износу. Диаграмма рентгеновской дифракции продукта реакции свидетельствовала о том, что продукт представляет собой орторомбический борид хрома. Размер (~ 1–2 мкм) частиц CrB подтверждается FESEM- и ТЕМ-изображениями. Твердотельные реакции, проведенные в герметических автоклавах, обеспечили альтернативный, удобный, экологически чистый путь производства CrB.